Pengaruh Penggunaan Media Animasi Pengenalan Kegiatan Berwudhu Pada Anak Kelompok B TK Uswatun Hasanah Padang - Safitri, Desnita Riana; Anggraini, Vivi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
This research was conducted with the aim of knowing how much influence the use of animated media had on the introduction of ablution activities to group B children at Uswatun Hasanah Kindergarten, Padang City. This type of research is a quantitative research with an experimental method with a one group pre-test post-test design model. Data collection techniques in the form of tests, observations, and documentation. The population in this study were all students of the Uswatun Hasanah Kindergarten, Padang City, totaling 46 children. While the sample numbered 32 children, 16 children in class B1 and 16 children in class B3. The data analysis used is the normality test, homogeneity, t-test, and also the effect size. The results showed that the experimental class obtained an average value of 34.81 while the control class obtained 27.75. Then, from the calculation of the influence test, a value of 1.907 is obtained which is included in the strong category. Thus the animation media has a significant influence on the child's ability to perform ablution and gives more influence than the control class which uses image media